Technology Integration Strategies for Teaching the Water Cycle: A Case Study in Fifth-Grade Science Learning - Rahayu, Ai Hayati; Widodo, Ari; Saud, Udin Syaefudin; Muslim, Muslim (PrimaryEdu : Journal of Primary Education, 2025)
This study aims to analyze teachers' strategies in integrating technology into the teaching of the water cycle material to enhance students' understanding and support 21st-century competencies, such as critical thinking, creativity, and collaboration. Using a qualitative case study approach, the research involved four teachers teaching 5th-grade elementary school students in Sumedang Regency. The teachers had previously received TPACK training using a collaborative, practical, and reflective approach. Data were collected through observations, in-depth interviews with teachers, and analysis of instructional documents.The findings reveal that teachers utilized various technological media, such as animated videos, digital simulations, and interactive PowerPoint presentations, to explain the water cycle concepts in a more engaging and comprehensible manner. Additionally, online learning platforms were employed to facilitate group discussions and student collaboration. These strategies not only improved students' understanding of the water cycle but also fostered 21st-century skills, such as collaboration, problem-solving, and creativity. However, challenges such as limited access to technology and students' digital literacy need to be addressed. This study recommends the principles of collaboration, practice, and reflection in conducting intensive training for teachers to enhance their ability to effectively utilize technology in the learning process.